KECEMASAN ORANG TUA PADA ANAK DENGAN THALASEMIA DI POLI ANAK RUMAH SAKIT UMUM DAERAH H. ABDUL MANAP KOTA JAMBI TAHUN 2015 - Reta Renylda (Universitas Batanghari Jambi, 2018)
Children with thalassemia must undergo blood transfusions to sustain life and routinely done in periods of continuous lama.Pengobatan will have an impact on psychosocial problems in the family, especially in the elderly. Parents will face a backlash in any care and treatment such as guilt, anxiety, fear, sadness, economic problems and worry about not getting the proper care and treatment.This research is a quantitative descriptive research that aims to describe the level of anxiety of parents of children with thalassemia in Poly Children's Hospital. H. Abdul Manap Jambi City in 2015. The population in this study were all parents whose children suffer from thalassemia as many as 56 people with a total sample of 33 people. This research was conducted on the 26th of June to July 26, 2015 with interview techniques and questionnaires. Results showed that of the 33 respondents, it is as much as 26 respondents (78.8%) had moderate anxiety level, as many as six respondents (18.2%) had mild anxiety level and 1 respondent (3%) had severe anxiety level. It is expected that nurses need to pay attention to and involve parents in performing nursing care in children with thalassemia, and improve the provision of information about the treatment of children to parents, so as to reduce anxiety.Keywords: Anxiety, Parents, Thalassemia